Physics Learning Innovation: Revealing the Potential of Lectora Inspire-Based Media with a Scientific Approach - Melinda, Elsa; Budiharti, Rini; Ekawati, Elvin Yusliana (Universitas Sebelas Maret, 2024)
The purpose of this research is to (1) Summarize the procedure for developing Lectora Insprire-based learning media with a scientific approach for learning high school physics on Dynamic Fluid material that meets good criteria, (2) Summarize the specifications of Lectora Insprire-based learning media with a scientific approach for learning high school physics on Dynamic Fluid material that has been developed, (3) Summarize the results of expert assessment of Lectora Insprire-based learning media with a scientific approach for learning high school physics on Dynamic Fluid material in terms of material, design, and language aspects. The research method used is Research and Development, which uses the ADDIE development model. The stages passed in this study are limited to the analysis stage, design stage, and development stage. Research data sources from supervisors, peers, high school physics teachers, and students of SMA Negeri 2 Magelang and SMA Negeri 4 Magelang. The data collection technique used in this research is distributing needs and assessment questionnaires. The analysis techniques used are qualitative analysis and quantitative analysis. The specifications of the developed media are published in .exe format, and there are features in the form of menus to go to specific pages. They are equipped with simulations and interactive questions and can be run offline. The results of the media assessment developed meet the criteria of excellent assessment given by the supervisor, peers, high school physics teachers, and high school students in class XI. This research can be the basis for developing Lectora Inspire-based learning media with a scientific approach to Dynamic Fluid material.